A subproject-based quota approach for life cycle carbon assessment at the building design and construction stage in China. (November 2020) - Zhang, Xiaocun; Zhang, Xueqi
Abstract: Recent research has focused on life cycle assessment of building embodied emissions, owing to the considerable influence on carbon reduction policies. Various methods have been proposed for the emission assessment, yet it is still difficult for building designers and engineers to implement the calculation in the design and construction stage owing to the complexity in data analysis. In this context, the present study proposed a subproject-based approach, and develop the building emission quota accordingly. Compared with conventional process-based analysis, the necessity and organization of the emission quota were underlined from the perspectives of scopes, inventory, and data structure. Based on the proposed quota, a calculator was developed and a case study was made on a residential building to examine the reliability and efficiency of the approach. The results indicated that, embodied emissions according to the proposed quota were consistent with the conventional analysis within the same system boundary. Furthermore, the application scopes and relevant advantages of adopting the emission quota were discussed. Overall, this study can promote the efficiency and reduce the difficulty in building emission assessment, and therefore be useful to low-carbon design and construction. Highlights: Proposed emission quota system for the emission assessment based on subprojects. Programmed calculator for data query, modification, maintenance, and analysis. Case study compares the proposed quota and conventional scope-based analysis. Discussion on the scopes of application shows the advantages of the emission quota.